2008
DOI: 10.2147/ijn.s3728
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hydrogen peroxide with chemiluminescent micelles

Abstract: Abstract:The overproduction of hydrogen peroxide is implicated in the progress of numerous life-threatening diseases and there is a great need for the development of contrast agents that can detect hydrogen peroxide in vivo. In this communication, we present a new contrast agent for hydrogen peroxide, termed peroxalate micelles, which detect hydrogen peroxide through chemiluminescence, and have the physical/chemical properties needed for in vivo imaging applications. The peroxalate micelles are composed of amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 20 publications
0
35
0
2
Order By: Relevance
“…In this study, the molar ratio of cyclohexanedimethanol to HBA was decided after the careful consideration of stability in aqueous environments and reactivity to H 2 O 2 [6,16]. It has been reported that the aromatic peroxalate compounds instantaneously react with H 2 O 2 specifically to decompose into carbon dioxide, and rapidly degrade under aqueous conditions via hydrolysis [6,23,24]. In contrast, polyoxalate with aliphatic peroxalate ester has low reactivity to H 2 O 2 and undergo slow hydrolytic degradation under aqueous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the molar ratio of cyclohexanedimethanol to HBA was decided after the careful consideration of stability in aqueous environments and reactivity to H 2 O 2 [6,16]. It has been reported that the aromatic peroxalate compounds instantaneously react with H 2 O 2 specifically to decompose into carbon dioxide, and rapidly degrade under aqueous conditions via hydrolysis [6,23,24]. In contrast, polyoxalate with aliphatic peroxalate ester has low reactivity to H 2 O 2 and undergo slow hydrolytic degradation under aqueous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, peroxalate nanoparticles were fabricated and used as a chemiluminescence probe to detect H 2 O 2 activity in inflammation and infection model in vivo. 18,45,46 Oxazine conjugated nanoparticles have been synthesized and used for ex vivo detection of . Fibrin-affinity probes were used to assess acute implant-mediated edema formation and fibrin deposition.…”
Section: Imaging the Release Of Inflammatory Productsmentioning
confidence: 99%
“…Bioanalytical approaches for detection of H 2 O 2 described in the literature include chemiluminescence, 6 fluorescence, 7 and electrochemistry. 8,9 The latter approach is particularly attractive due to simplicity and reliability of measurements, and the possibility for miniaturization.…”
Section: Introductionmentioning
confidence: 99%